Electrical characterization of amorphous Al2O3 dielectric films on n-type 4H-SiC - R. Y. Khosa; E. B. Thorsteinsson; M. Winters; N. Rorsman; R. Karhu; J. Hassan; E. Ö. Sveinbjörnsson (AIP Advances, 2018)
We report on the electrical properties of Al2O3 films grown on 4H-SiC by successive thermal oxidation of thin Al layers at low temperatures (200°C - 300°C). MOS capacitors made using these films contain lower density of interface traps, are more immune to electron injection and exhibit higher breakdown field (5MV/cm) than Al2O3 films grown by atomic layer deposition (ALD) or rapid thermal processing (RTP). Furthermore, the interface state density is significantly lower than in MOS capacitors with nitrided thermal silicon dioxide, grown in N2O, serving as the gate dielectric. Deposition of an additional SiO2 film on the top of the Al2O3 layer increases the breakdown voltage of the MOS capacitors while maintaining low density of interface traps. We examine the origin of negative charges frequently encountered in Al2O3 films grown on SiC and find that these charges consist of trapped electrons which can be released from the Al2O3 layer by depletion bias stress and ultraviolet light exposure. This electron trapping needs to be reduced if Al2O3 is to be used as a gate dielectric in SiC MOS technology.